Inflammation and Pancreatic Cancer: Recent Development with Focusing on Potential New Drug Targets - Uomo, Generoso; Laghi, Luigi; Pezzilli, Raffaele (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2011)
Chronic inflammation has been identified as a significant factor in the carcinogenesis of various tumors, including pancreatic cancer. Both hereditary and classical forms of chronic pancreatitis are associated with an increased risk of developing pancreatic cancer. Cytokines and other mediators of the inflammatory process together with an upregulation of pro-inflammatory pathways play a pivotal role in oncogenesis' stimulation, tumor growth and metastasis. The presence of a strong desmoplastic reaction within and around pancreatic cancer cells renders the proteolytic degradation of extracellular matrix components an essential process for tumor invasion and metastasis. Various classes of proteases produced by the pancreatic acinar cells are involved in these proteolytic events. The multiple link between inflammation and pancreatic cancer may represent the basis for a novel antineoplastic strategy. Cytokines, proteases, reactive-oxygen-species, cyclooxygenase-2, nuclear-factor-κB and perixosome proliferator-activated receptor-γ may be a new molecular targets useful for therapeutic purpose.
Keywords: cytokines